2017
DOI: 10.1038/s41590-017-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis reveals the continuum of human lympho-myeloid progenitor cells

Abstract: The human hemopoietic progenitor hierarchy producing lymphoid and granulocytic-monocytic (myeloid) lineages is unclear. Multiple progenitor populations produce lymphoid and myeloid cells, but remain incompletely characterized. Here, we demonstrated cord blood lympho-myeloid containing progenitor populations - the lymphoid-primed multi-potential progenitor (LMPP), granulocyte-macrophage progenitor (GMP) and multi-lymphoid progenitor (MLP) - were functionally and transcriptionally distinct and heterogeneous at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
223
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(257 citation statements)
references
References 53 publications
14
223
3
1
Order By: Relevance
“…In experimental terms, this means that a phenotypically defined population does not contain a homogeneous population of multi-potent cells, but rather, a cross-section of cells primed by related but distinct developmental pathways that share a common, transient phenotype. [33][34][35][36] Entities such as the macrophage-dendritic cell progenitor (MDP) and common dendritic cell progenitor (CDP) are evanescent. Although bi-potential and tri-potential cells exist, profiling of > 2000 clonal outputs from the entire range of human progenitors does not find any significant populations corresponding to human MDP or CDP.…”
Section: Analysis Of Human Dendritic Cells Monocytes and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental terms, this means that a phenotypically defined population does not contain a homogeneous population of multi-potent cells, but rather, a cross-section of cells primed by related but distinct developmental pathways that share a common, transient phenotype. [33][34][35][36] Entities such as the macrophage-dendritic cell progenitor (MDP) and common dendritic cell progenitor (CDP) are evanescent. Although bi-potential and tri-potential cells exist, profiling of > 2000 clonal outputs from the entire range of human progenitors does not find any significant populations corresponding to human MDP or CDP.…”
Section: Analysis Of Human Dendritic Cells Monocytes and Macrophagesmentioning
confidence: 99%
“…33,34,37 In contemporary models, lymphoid-primed multipotent progenitors are at the apex of all myeloid and lymphoid lineages. 34,36 The important consequence of this is that it is no longer necessary to puzzle over the apparent 'dual' lymphoid and myeloid origin of DC, because DC are a product of the core lympho-myeloid pathway in which both traits may be expressed by emerging progeny.…”
Section: Analysis Of Human Dendritic Cells Monocytes and Macrophagesmentioning
confidence: 99%
“…The observed heterogeneity between patients is directly derived from differences in the LSC compartment in terms of lineage maturation, potency and the underlying molecular aberrations. A recent study suggested that normal differentiation is represented by a continuum observed on the single cell level (Karamitros et al , ), rather than discrete steps, making the matter even more complex. In addition, a variable degree of intra‐patient heterogeneity may arise from co‐existing subclones, which are frequently observed in AML (Cancer Genome Atlas Research Network, ).…”
Section: The Present Toolbox For Aml Lsc Characterisationmentioning
confidence: 99%
“…When cells culture in ultra-low plates, cells do not adhere to the bottom of wells. Methylcellulose-based semi solid media have also been used in a colony formation assay in some recent studies (de Sio et al, 2017;Karamitros et al, 2018).…”
Section: Colony Formation Assaymentioning
confidence: 99%